Welfare state ideologies and long-term care regimes: challenges of working age carers with dependent relatives in Macedonia - Gerovska Mitev, Maja; Bornarova, Suzana (My University, 2017)
The aim of the paper is twofold: to analyse to what extent the concept of “reconciliation between professional and private life” fits into the tradition and scope of the long-term care (LTC) regimes in Europe, as well as to provide insight into the challenges of working age carers in Macedonia. The initial hypothesis of the paper is to identify whether the lack of support towards carers in some of the European long-term care regimes is associated with the tradition and/or welfare ideology in which LTC systems were created. For that purpose, a comparative analysis will be undertaken of LTC schemes in four different welfare state regimes (Esping-Andersen, 1990) i.e. in Sweden, Germa-ny, UK and Italy. The analysis will take into consideration the founding principles of the LTC regimes, welfare ideology as well as the scope of support provided to carers in the respective countries. The second part of the paper will provide insight into challenges faced by working age carers with dependent relatives in Macedonia. This country case study will provide insight into the challenges faced by the caregivers due to lack of balance between the overall package of social protection, health and employment measures. Hence, this part will try to support the evidence that in countries where labour market support of the carers’ is marginalised, carers’ are more vulnerable category, especially in relation to employment and decent living standards.